Addressing a long term residential-care routing problem - Lopes, M. J.; Pita, P.; Pereira, Rafael; Catarino, P.; Teixeira, A.; Godinho, M. T. (ORAHS - OR Applied to Health Systems, 2022)
We address a challenge proposed by the Unidade Local de Sa´ude do Baixo Alentejo. The Unidade Local de Saúde do Baixo Alentejo (ULSBA) manages the national health service in the Alentejo’s Region, Portugal. Its Tansport Department (NCT) is responsible for scheduling all the required trips for that day. The required trips may be as diverse as taking the CEO to a meeting, providing the transport of medicines, or organizing home healthcare services. The aim is to find a way to change the operating system now available to an easier one, preferably highly automated and requiring few user intervention. During the process, it was agreed that this (huge) problem would be addressed in stages – in this work we study the Residential Long-term Care Unit routing needs. The Residential Long-term Care Unit provides home support to patients with conditions that require specialized healthcare, but do not require hospitalization. The Unit is made up of multidisciplinary healthcare teams that pay visits to the patients in their homes. Due to medical reasons or self-convenience of the patients, some of the visits have to be paid in given time-slots. The associated routing problem consists in finding the optimal set of routes that allows to visit all the patients while fulfilling the time requirements. We propose an integer linear programming approach to this problem. Computational results will be presented.